2012
DOI: 10.1002/anie.201108800
|View full text |Cite
|
Sign up to set email alerts
|

A Statically Oleophilic but Dynamically Oleophobic Smooth Nonperfluorinated Surface

Abstract: Extensive research on the preparation of superhydrophobic surfaces has been reported in the past decade, ranging from basic research to practical applications. Such surfaces usually exhibit water contact angles (CAs) larger than 1508. However, studies on superoleophobic surfaces, on which nonpolar (NP) liquid droplets (in particular, small volumes ca. 3-5 mL) that have appreciably low surface tensions (LSTs) can easily roll across and off, and which have a minimum tilt angle (TA) for droplet motion of less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(205 citation statements)
references
References 45 publications
12
189
0
Order By: Relevance
“…Even after immersing the surface for 1 h into the 10% cow blood plasma sample, the CA only dropped two Langmuir XXXX, XXX, XXX−XXX degrees to 150°( Figure 2H). We rationalize this excellent antifouling by the combination of the superhydrophobicity and the smoothness of this surface that is apparent from the small sliding angle 50 (6°) and the low contact angle hysteresis (8°), 52 both of which are also favorable for releasing any weakly adhered fouling proteins. 53,54 In contrast, on the flat PMAF17 brush modified surface the static water CA decreases from 118°t o 109°upon interaction with BSA and to 94°with blood plasma, illustrating that some protein adsorption happens on this surface ( Figure 2B, B1, and G).…”
Section: Resultsmentioning
confidence: 83%
“…Even after immersing the surface for 1 h into the 10% cow blood plasma sample, the CA only dropped two Langmuir XXXX, XXX, XXX−XXX degrees to 150°( Figure 2H). We rationalize this excellent antifouling by the combination of the superhydrophobicity and the smoothness of this surface that is apparent from the small sliding angle 50 (6°) and the low contact angle hysteresis (8°), 52 both of which are also favorable for releasing any weakly adhered fouling proteins. 53,54 In contrast, on the flat PMAF17 brush modified surface the static water CA decreases from 118°t o 109°upon interaction with BSA and to 94°with blood plasma, illustrating that some protein adsorption happens on this surface ( Figure 2B, B1, and G).…”
Section: Resultsmentioning
confidence: 83%
“…Recently, the idea of introducing repulsive liquids into constructing superantiwetting surfaces has aroused increasing attention. [58][59][60] More interesting discoveries may appear in this area.…”
Section: Superoleophobic Surfaces In Watermentioning
confidence: 99%
“…Poly-L Loop and poly-L Linear that consists of low molecular weight PDMS polymers showed similar morphology dependence. In contrast, Hozumi and co-workers 31 reported that linear PDMS polymer brushes are smooth and have a reduced hysteresis. This discrepancy may arise from a difference in grafting density.…”
Section: Materials Wettabilitymentioning
confidence: 91%